Human rhinovirus‐specific CD8 T cell responses target conserved and unusual epitopes. Issue 1 (23rd November 2020) - Gomez‐Perosanz, Marta; Sanchez‐Trincado, Jose L.; Fernandez‐Arquero, Miguel; Sidney, John; Sette, Alessandro; Lafuente, Esther M.; Reche, Pedro A.
Abstract: Human Rhinovirus (HRV) is a major cause of common cold, bronchiolitis, and exacerbations of chronic pulmonary diseases such as asthma. CD8 T cell responses likely play an important role in the control of HRV infection but, surprisingly, HRV‐specific CD8 T cell epitopes remain yet to be identified. Here, we approached the discovery and characterization of conserved HRV‐specific CD8 T cell epitopes from species A (HRV A) and C (HRV C), the most frequent subtypes in the clinics of various pulmonary diseases. We found IFNγ‐ELISPOT positive responses to 23 conserved HRV‐specific peptides on peripheral blood mononuclear cells (PBMCs) from 14 HLA I typed subjects. Peptide‐specific IFNγ production by CD8 T cells and binding to the relevant HLA I were confirmed for six HRV A‐specific and three HRV C‐specific CD8 T cell epitopes. In addition, we validated A*02:01‐restricted epitopes by DimerX staining and found out that these peptides mediated cytotoxicity. All these A*02:01‐restricted epitopes were 9‐mers but, interestingly, we also identified and validated an unusually long 16‐mer epitope peptide restricted by A*02:01, HRVC1791‐1806 (GLEPLDLNTSAGFPYV). HRV‐specific CD8 T cell epitopes describe here are expected to elicit CD8 T cell responses in up to 87% of the population and could be key for developing an HRV vaccine.